Understanding the Sufism and Islamic Jurisprudence (Fiqh) Reasoning In the Terms of Religious mModeration: Perennial Philosophical Perspective - Ismail, Ismail (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
The truth claim phenomenon in understanding religious teachings often occurs in human life. It needs to be avoided by finding solutions. This article aimed to comprehend religious teachings using the reasoning of Sufism and Islamic jurisprudence (Fiqh) in a balanced way in order to avoid distorted understanding due to the interpretation of different religious teachings. Sufism and Fiqh reasoning are described in order to explain the meeting point between them. Sufism historically has developed since the beginning of Islam (I and II centuries H/8 AD), as well as Fiqh has developed through four periods, namely the Prophet, the Companions (Khulafaur Râsyidîn), the Ijtihad, and the Taklid period. Life requires a moderate attitude in religion. The practice of Sufism empirically is considered as a cure for mental suffering in the midst of a materialistic-hedonistic humanitarian crisis. On the other hand, the practice of Fiqh focuses on the issue of haliyah-`amliyah-furu`iyah ijtihad. At the empirical level, Sufism and Fiqh are interrelated and integrated. Therefore, there is always a meeting point that unites Sufism and Fiqh reasoning. Quoting the opinion of Imam Shafi`i